2020
DOI: 10.1016/j.ejca.2020.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of severe acute respiratory syndrome coronavirus 2 infection in patients with metastatic castration-resistant prostate cancer

Abstract: Background Patients with cancer are at increased risk of complicated severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection, but it is still unclear if the risk of mortality is influenced by cancer type or ongoing anti-cancer treatments. An interesting debate concerning the potential relationship between androgen deprivation therapy (ADT) and SARS-CoV-2 infection has recently been opened in the case of prostate cancer (PC), and the aim of this multi-centre cohort study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 14 publications
2
27
1
Order By: Relevance
“…Of these five studies, only two studies provided information on the hospitalization and mortality rates in COVID-19-positive PCa patients and were used for analysis ( Figure 8 ). These two studies reported a higher incidence of hospitalization and mortality in COVID-19-positive PCa patients, similar to our study [ 12 , 15 ] ( Figure 8 ). Studies used for comparisons, presented in Figure 7 and Figure 8 , include data from the Turkish National Registry Data [ 21 ], COVID-19 and Cancer Consortium (CCC19) Database [ 14 ], Detroit study [ 17 ], a single-center retrospective study from New York City [ 22 ], and data from Veneto hospitals in Italy [ 15 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Of these five studies, only two studies provided information on the hospitalization and mortality rates in COVID-19-positive PCa patients and were used for analysis ( Figure 8 ). These two studies reported a higher incidence of hospitalization and mortality in COVID-19-positive PCa patients, similar to our study [ 12 , 15 ] ( Figure 8 ). Studies used for comparisons, presented in Figure 7 and Figure 8 , include data from the Turkish National Registry Data [ 21 ], COVID-19 and Cancer Consortium (CCC19) Database [ 14 ], Detroit study [ 17 ], a single-center retrospective study from New York City [ 22 ], and data from Veneto hospitals in Italy [ 15 ].…”
Section: Resultssupporting
confidence: 91%
“…A PubMed search of “prostate cancer” and “COVID-19” resulted in nine studies [ 2 , 12 , 13 , 14 , 15 , 16 , 17 , 21 , 22 ]. After reviewing the nine publications, which did include relevant information on the incidence of COVID-19 in prostate cancer patients, we excluded four studies [ 2 , 12 , 13 , 16 ] that did not include details of the reference group in their analysis. The five studies that were selected reported the incidence rate of COVID-19 in patients with prostate and other genitourinary cancer ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. After applying the inclusion and exclusion criteria six studies (Patel et al updated their study in 2021 [18,21]) were included for systematic review; Caffo et al was excluded from the meta-analysis due to the lack of a control group [22].…”
Section: Selection Processmentioning
confidence: 99%
“…No PCa risk or stage was specified, but the authors concluded that PCa patients on ADT have a significantly lower risk of COVID-19 infection (OR 4.05; 95% CI 1.55 to 10.59). Caffo et al [45] performed a multicenter retrospective study in Italy (20 oncological centers), including 1433 men with metastatic castration-resistant PCa (mCRPC), who continued oncological consultation during the pandemic (February to June 2020); 34 (2.3%) developed SARS-CoV-2 infection, all of them with ADT, 9 with concomitant chemotherapy, and 19 with concomitant androgen-receptor-axis-targeted therapies (ARAT). Thirteen patients (38.2%) died, 85.7% of whom had previously received 2 or more mCRPC therapies.…”
Section: Androgen Deprivation Therapy In Pcamentioning
confidence: 99%